In Vitro Oncolytic activity of non-virulent Newcastle Disease Virus LaSota Strain against Mouse mammary adenocarcinoma - Hassan, Sarah A.H.; Allawe, Aida B.; Al-Shammari, Ahmed Majeed (Iraqi Journal of Science, 2020)
Newcastle disease virus (NDV) is a wide-spectrum anti-tumor agent. The oncolytic selectivity of NDV, a family of Paramyxoviridae, depends on the differential type of inducing different death pathways. This work was conducted to further understand the oncolytic effect of LaSota strain. A mouse breast cancer model (Murine mammary adenocarcinoma cell line AMN3) was used in this study. Methyl Thiazolyl Tetrazolium (MTT) viability assay tested different NDV multiplicity of infection (MOI) values on mouse mammary adenocarcinoma cells incubated for 72 hours post-infection. The IC50 values and anti-tumor activity of LaSota strain against AMN3 cell line were determined. Following Hematoxylin and Eosin Stain, we examined the morphological modifications of IC50 along with 10 MOI values of NDV. The induction of NDV apoptosis in AMN3 cells was investigated using the technique of staining acridine orange and propidium iodide (AO / PI). Immunocytochemistry assay was performed using anti-NDV mAbs and caspases 8 and 9 to study NDV replication and apoptosis induction mechanisms. The lentogenic LaSota NDV strain, a live vaccine, demonstrated the oncolytic effect on mammary cancer cells of the AMN3 mouse and showed that LaSota strain triggered a dose-dependent increase in infected cells’ apoptosis relative to untreated mammary cancer cells. The immunocytochemistry study showed that NDV infected cells were positive for virus infection and that caspase9 in mouse mammary cancer cells after LaSota strain infection was significantly enhanced compared to caspase 8. In conclusions, NDV LaSota strain had oncolytic effects by destroying tumor cells and triggering the intrinsic apoptosis pathways in mouse mammary cancer cells. However, the mechanisms of the in vivo anti-tumor activity need to be better understood.